Recent Trends in Treatment and Fabrication of Plant-Based Fiber-Reinforced Epoxy Composite: A Review - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Natural fiber (NF) is one of the many resources that nature has provided. NFs decompose quickly and are biodegradable, renewable, and cost-effective. It may be scavenged from a variety of plant and animal sources. They are employed as reinforcing materials in polymers for NF composite development. Because of its environmental friendliness and long-term survivability, NF is growing in appeal among academics and researchers for usage in polymer composites. This study aims to offer a thorough evaluation of the most suitable and widely utilized natural fiber-reinforced polymer composites (NFPCs), along with their manufacture, processing, and applications. It also defines several external treatments of NF and their influence on the characteristics of NFPCs. The characteristics of NFPCs are affected by fiber supply, fiber type, and fiber structure. Numerous physical and chemical treatments were tested to see how they affected the thermal and strength properties of natural fiber-reinforced thermoplastic and thermosetting composites. Several polymer composite fabrication techniques were also studied. NFPCs have several disadvantages, notably low fire protection, poor strength properties, and greater moisture absorption, which have prevented their application. It is shown how NFPCs are employed in a variety of industries, particularly automotive and research industries. The review discovered that intentionally changing the regular fiber enhanced the thermochemical and physico-mechanical properties of the NFPCs by means of improving the grip between the fiber surface and the polymer framework. This study aims to provide important and fundamental facts on NF and their composites, which will aid in new investigations, the creation of a creative framework for polymer composite types, and the achievement of Sustainable Development Goals. © 2023 by the authors.